A study on the Human Resource Information Systems (HRIS) In Universiti Malaysia Kelantan (UMK) and its impact on the employees satisfaction / Mohd Norhafizan Muhammad - Muhammad, Mohd Norhafizan (2011)
The aim of this study was to examine the Human Resource Information Systems (HRIS) in Universiti Malaysia Kelantan and its impact on the employee satisfaction. There are three (3) independent variables that been studied, which were system quality, information quality and organizational performance. This study also was conduct to confirm the predetermine factors contribute to the employee satisfaction towards Human Resource Information Systems (HRIS) in Universiti Malaysia Kelantan. Moreover, questionnaire had been used in order to get feedback from employees. Researcher had distributed 100 questionnaires to Universiti Malaysia Kelantan administration staffs especially the Registrar Department. The sampling is convenient sampling. The method that been use are simple convenient sampling. The data collected was then tested on its frequency and reliability analysis. simple regression analysis, t-test analysis and f-test analysis were used to test the hypothesis in this study. The finding on reliability was excellent and it considers that all dependent are acceptable. The findings of this paper suggest three factors are significant factors for explaining employee satisfaction towards Human Resource Information System (HRIS) in Universiti Malaysia Kelantan (UMK). Based from the results obtained in this study, researcher suggests some recommendations like make the system more friendly user and system up-to-date time to time that can help the management in Universiti Malaysia Kelantan to assist the current and future potential system management